Breeding and Productive Performance of Three Breeds of Rabbit in South-West Nigeria (Global Journal of Science Frontier Research, 2012)
Three breeds of rabbit-Giant Flemish (GF), Chinchilla (CH) and Rex (RX) were procured from a reputable farm in South-West Nigeria for crossbreeding to determine the productive performance of each breed and with the aim of selecting the most superior genotype(s) for increased rabbit production. Animals were paired and the pairing resulted into six genetic groups. A total of twenty-one animals (18 does and 3 bucks) were involved. Data on productive traits such as litter size at birth and at weaning, litter weight at birth and at weaning, gestation length in each female breed, percentage mortality during pre-weaning in each group and percentage survivability till weaning were collected for each crossing. Results shows that mean litter size at birth in the genetic groups ranged from 1.67±0.33 to 4.00±0.00 and mean litter size at weaning was between 1.67±0.33 and 3.00±0.58 in groups CH vs. RX and RX vs. GF, respectively. Mean litter weight at birth was between 39.18±0.74 and 43.56±0.88 g. In the genetic groups with the exception of CH vs. RX, mean litter size at birth (MLS@B) was greater than mean litter size at weaning (MLS@W). Gestation length of the breeds of rabbit used ranged from 29.67±0.66 to 30.33±0.67 days. Genetic group CH vs. GF has the highest mean litter weight at birth and highest mean litter weaning weight.
Keywords: Breeding; hierarchic design; Nigeria; performance; rabbit